Mechanical Properties of Thixoformed 7075 Feedstock Produced Via The Direct Thermal Method - Asnul Hadi, Ahmad; Naher, Sumsun; Brabazon, Dermot (Trans Tech Publications, Switzerland, 2015)
This paper presents an overview of measured mechanical properties of thixoformed aluminium 7075 feedstock produced by the direct thermal method (DTM). The DTM feedstock billets were processed with a pouring temperature of 685 °C and holding periods of 20 s, 40 s and 60 s before being quenched and subsequently thixoformed. A conventionally cast feedstock billet was produced with a pouring temperature of 685 °C and was allowed to solidify without quenching. The feedstock billets were later formed by an injection test unit in the semi-solid state. Tensile testing was then conducted on the thixoformed feedstock billets. Tensile properties for 7075 DTM thixoformed feedstock billets were found significantly influenced by the thixoformed component density. Samples with longer holding times were found to have higher density and higher tensile strength.